Susceptibility of Commensal E. coli Isolated from Conventional, Antibiotic-Free, and Organic Meat Chickens on Farms and at Slaughter toward Antimicrobials with Public Health Relevance - Laura Musa; Patrizia Casagrande Proietti; Maria Luisa Marenzoni; Valentina Stefanetti; Tana Shtylla Kika; Francesca Blasi; Chiara Francesca Magistrali; Valeria Toppi; David Ranucci; Raffaella Branciari; Maria Pia Franciosini (MDPI AG, 2021)
The spread of resistant bacteria from livestock to the food industry promoted an increase of alternative poultry production systems, such as organic and antibiotic-free ones, based on the lack of antimicrobial use, except in cases in which welfare is compromised. We aimed to investigate the antibiotic susceptibility of commensal Escherichia coli isolated from organic, antibiotic-free, and conventional broiler farms and slaughterhouses toward several antimicrobials critically important for human health. To assess antimicrobial susceptibility, all E. coli isolates and extended spectrum beta-lactamase (ESBL) E. coli were analysed by the microdilution method. The prevalence of tigecycline, azithromycin and gentamicin E. coli-resistant strains was highest in organic samplings. Conversely, the lowest prevalence of resistant E. coli strains was observed for cefotaxime, ceftazidime and ciprofloxacin in organic systems, representing a significant protective factor compared to conventional systems. All E. coli strains were colistin-susceptible. Contamination of the external environment by drug-resistant bacteria could play a role in the presence of resistant strains detected in organic systems. Of interest is the highest prevalence of cephalosporin resistance of E. coli in conventional samplings, since they are not permitted in poultry. Our results suggest that monitoring of antibiotic resistance of the production chain may be helpful to detect "risks" inherent to different rearing systems.